HIV Related Stigma among Healthcare Providers: Opportunities for Education and Training. (July 2022) - Spence, Amanda Blair; Wang, Cuiwei; Michel, Katherine; Ocampo, Joanne Michelle; Kharfen, Michael; Merenstein, Daniel; Goparaju, Lakshmi; Kassaye, Seble
Background: HIV-stigma can influence engagement in care and viral suppression rates among persons living with HIV (PLWH). Understanding HIV-provider level stigma and its associated factors may aid in development of interventions to improve engagement in care.Methods: We assessed HIV-related stigma, provider knowledge, and practices and beliefs among healthcare providers using an online survey tool. Generalized linear modeling was used to determine factors associated with HIV-stigma score.Results: Among 436 participants, the mean age was 42.3 (SD 12.3), 70% female, 62% white, 65% physicians, and 44% worked at an academic center. The mean HIV Health Care Provider Stigma Scale (HPASS) score was 150.5 (SD 18.9, total = 180 [higher score = less stigma]) with factor subscale scores of 67.1 (SD 8.2, total = 78) prejudice, 51.3 (SD 9.7, total = 66) stereotyping, and 32.1 (SD 5, total = 36) discrimination. Female sex and comfort with talking about sex and drug use had 4.97 (95% CI 0.61, 9.32) and 1.99 (95% CI 0.88, 3.10) estimated higher HPASS scores. Disagreement/strong disagreement versus strong agreement with the statement that PLWH should be allowed to have babies and feeling responsible for talking about HIV prevention associated with −17.05 (95% CI −25.96, −8.15) and −2.16 (95% CI −3.43, −0.88) estimated lower HPASS scores.Conclusions: The modifiable factors we identified as associated with higher HIV related stigma may provide opportunities for education that may ameliorate these negative associations.